2018
DOI: 10.1590/1981-6723.0716
|View full text |Cite
|
Sign up to set email alerts
|

Potencial de desenvolvimento de Lasioderma serricorne (Fabricius, 1792) (Coleoptera: Anobiidae) em dietas contendo soja

Abstract: Este é um artigo publicado em acesso aberto (Open Access) sob a licença Creative Commons Attribution, que permite uso, distribuição e reprodução em qualquer meio, sem restrições desde que o trabalho original seja corretamente citado. Potencial de desenvolvimento de Lasioderma serricorne (Fabricius, 1792)(Coleoptera: Anobiidae) em dietas contendo soja Potential for the development of Lasioderma serricorne (Fabricius, 1972) (Coleoptera: Anobiidae) in diets with soybean ResumoLasioderma serricorne é uma praga c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…The main pests that occur in storage of soybean seeds are the Coleoptera Lasioderma serricorne, Cryptolestes ferrugineus, Oryzaephilus surinamensis, Sitophilus oryzae, Rhyzopertha dominica, Tribolium castaneum, Ahasverus advena, and Lophocateres pusillus, and the Lepidoptera Ephestia elutella, Ephestia cautella, and Sitotroga cerealella (Lorini, 2012;Lorini et al, 2015). L. serricorne develops in soybean seeds during the storage period, justifying routine fumigation with phosphine to prevent losses (Ferri et al, 2018). Seed fumigation with the use of phosphine gas (PH 3 ) is a technique that has been used for several years on several products, however, only recently in storage of soybean.…”
Section: Introductionmentioning
confidence: 99%
“…The main pests that occur in storage of soybean seeds are the Coleoptera Lasioderma serricorne, Cryptolestes ferrugineus, Oryzaephilus surinamensis, Sitophilus oryzae, Rhyzopertha dominica, Tribolium castaneum, Ahasverus advena, and Lophocateres pusillus, and the Lepidoptera Ephestia elutella, Ephestia cautella, and Sitotroga cerealella (Lorini, 2012;Lorini et al, 2015). L. serricorne develops in soybean seeds during the storage period, justifying routine fumigation with phosphine to prevent losses (Ferri et al, 2018). Seed fumigation with the use of phosphine gas (PH 3 ) is a technique that has been used for several years on several products, however, only recently in storage of soybean.…”
Section: Introductionmentioning
confidence: 99%
“…Relative humidity (RH) in the range of 65 to 75% does not prevent insect development, unless the substrate is destroyed by fungal growth (EDDE, 2019). FERRI et al (2018), studying the development of L. serricorne in soy-based products at a temperature of 27°C and RH at 60%, found that the duration of the egg to adult phases had the highest peak at 49 days after infestation of insects. MAHROOF; PHILLIPS (2008), studying the development parameters of L. serricorne in seven food sources at a temperature of 28°C and 60% RH, observed that the development duration was 46 days.…”
mentioning
confidence: 99%
“…Therefore, knowledge of the insect's biology and behavior in different hosts is the first important step towards solving any agricultural pest problems and defining strategies for their management in the storage of grains and their derivatives (FERRI et al, 2018). The phosphine fumigation method is the most effective and widely used, at the same time as it allows residue-free treatment of the grains.…”
mentioning
confidence: 99%
“…e Rhyzopertha dominica (Fabricius). Existem também aquelas que se alimentam das partes externas do grão e posteriormente atacam as partes internas, sem completar seu desenvolvimento, como a Plodia interpunctella (Hübner) (LORINI et al 2015(LORINI et al , 2018.…”
Section: Pragas De Produtos Armazenadosunclassified
“…As larvas são de coloração branca com tons de creme e rosado em algumas partes do corpo, atingindo até 15 mm de comprimento. Possuem as bordas dos espiráculos abdominais uniformemente espessadas, apresentando três pares de pernas torácicas e quatro pares de falsas pernas no abdome (ATHIÉ; PAULA, 2002;REES, 2007;LORINI et al 2015LORINI et al , 2018.…”
Section: Lasioderma Serricorne (Fabricius 1792) (Coleoptera: Ptinidae)unclassified